2019
DOI: 10.1021/acs.iecr.9b00415
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into Excellent Catalytic Performance of the Ce-Modified Catalyst for NO Oxidation

Abstract: Diesel exhaust has recently become a severe problem, and diesel oxidation catalyst (DOC) installed in the diesel exhaust treatment system is used to reduce automobile pollution containing CO, hydrocarbons (HC), and NO. In this work, for the purpose of elucidating the effect of ceria addition on the catalytic performance of Pt-based DOC in CO, HC, and NO oxidation reactions, a range of catalysts were prepared by impregnation method. Among them, the Pt/ 15CeSA catalyst showed excellent catalytic activity, and it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 64 publications
3
10
0
Order By: Relevance
“…The ratios of I D /I F2g are calculated as summarized in Table 1, which can reflect the relative concentration of oxygen vacancies in the catalysts. 38 They increase in the order of octahedrons < cubes < rods, consistent with previous reports. 24,39 The ratios of I D /I F2g suggest that CeMnO x rods and cubes possess more oxygen vacancies in the CeO 2 lattice compared to CeMnO x octahedrons on account of the interaction between Ce and Mn ions.…”
Section: Industrial and Engineering Chemistry Researchsupporting
confidence: 92%
“…The ratios of I D /I F2g are calculated as summarized in Table 1, which can reflect the relative concentration of oxygen vacancies in the catalysts. 38 They increase in the order of octahedrons < cubes < rods, consistent with previous reports. 24,39 The ratios of I D /I F2g suggest that CeMnO x rods and cubes possess more oxygen vacancies in the CeO 2 lattice compared to CeMnO x octahedrons on account of the interaction between Ce and Mn ions.…”
Section: Industrial and Engineering Chemistry Researchsupporting
confidence: 92%
“…260°C due to the co-presence of C 3 H 6 and NO at a high GHSV. The catalytic performance of Pd 1 @HEFO is comparable to Pt/ CeO 2 -SiAlO x regarded as a candidate of diesel oxidation catalyst (DOC) 50 and Pt/CeO 2 40 . Moreover, no obvious deactivation of CO, C 3 H 6 , and NO oxidation can be observed over Pd 1 @HEFO even after 10 h of reaction in Supplementary Fig.…”
Section: Synthesis and Characterizations As Illustrated Inmentioning
confidence: 98%
“…The oxidation of NO to NO 2 is also a key step both in the NOx reduction technologies and the nitric acid production. For example, the NH 3 -SCR reaction rate can be greatly enhanced if a fraction of NO is converted to NO 2 , and the increase of the NO 2 content greatly improves the efficiency of the reduction catalysts and also decreases aging of the catalysts. , Supported catalysts (included noble metals and metal oxides) are widely used in the catalytic oxidation of NO. However, these oxidation reactions are always conducted at high NO concentrations (up to hundreds ppm) and high temperature (about 423–723 K). In contrast, it was found that when the NO concentration was low to the ppb level, the heterogeneous reaction of NO on atmospheric particles was slow and supposed to hardly happen. , Therefore, the heterogeneous conversion of NO to NO 2 in the atmospheric chemistry has always been neglected.…”
Section: Introductionmentioning
confidence: 99%